ECOPRINT INTEGRATION FOR ENVIRONMENTAL CHARACTER EDUCATION IN AN ADIWIYATA SCHOOL: CASE STUDY OF SDN 1 SITIWINANGUN - kusuma, trio adi; Faiz, Aiman; Afendi, Arief Hidayat (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2025)
The increasing complexity of environmental crises, including climate change, pollution, and waste management, necessitates systematic and structured initiatives to address these challenges. Early environmental awareness is essential for fostering pro-environmental behavior. The Adiwiyata School Program offers a framework for integrating environmental values into elementary-level character education. This research examines the implementation of eco-printing, a natural dyeing technique that utilizes leaves and flowers, as a means to develop an environmentally conscious character at SDN 1 Sitiwinangun. A qualitative case study approach was employed, with data collected through participatory observation, semi-structured interviews, and documentation. The findings indicate that eco-printing functions as both a creative art activity and an effective educational medium for instilling values such as responsibility, collaboration, and environmental stewardship. The activity is incorporated into thematic learning and the Pancasila Student Profile (P5) project on Sustainable Lifestyle. The multisensory learning experience and active participation of the school community contribute to sustained behavioral change. Documented outcomes include enhanced waste management, conservation of natural resources, and the adoption of environmentally friendly practices at school and home. These results demonstrate that eco-printing is a transformative approach to environmental character education, consistent with the objectives of the Adiwiyata Program and the Sustainable Development Goals (SDGs). Therefore, educators, policymakers, and school leaders are strongly encouraged to adopt and integrate eco-printing more broadly as an educational strategy to promote ecological responsibility among students from an early age.